夢♥想 發問時間: 科學數學 · 6 年前

請問這一題數學一階微分整理後是什麼樣子?f'(1)帶進去等於

已知f(x)=(x^2+x+1)^2 ● (x-2)^4,請問f'(x)=?f'(1)=?

1 個解答

評分
  • 麻辣
    Lv 7
    6 年前
    最佳解答

    F(x) = (x^2+x+1)^2 * (x-2)^4 = A(x) * B(x)

    (1) F'(x)=?= A(x)*B'(x) + A'(x)*B(x)= (x^2+x+1)^2 * 4(x-2)^3 + 2(x^2+x+1)*(2x+1) * (x-2)^4= 2(x^2+x+1)(x-2)^3*[2(x^2+x+1) + (2x+1)(x-2)]= 2(x^2+x+1)(x-2)^3*(2x^2+2x+2 + 2x^2-3x-2)= 2(x^2+x+1)(x-2)^3*(4x^2-x)= 2x(4x-1)(x^2+x+1)(x-2)^3

    (2) F'(1)=? = 2*1*3*(1+1+1)*(-1)^3= -6*3= -18

還有問題?馬上發問,尋求解答。